2021
DOI: 10.1038/s41598-021-86535-1
|View full text |Cite
|
Sign up to set email alerts
|

Prunus Hexokinase 3 genes alter primary C-metabolism and promote drought and salt stress tolerance in Arabidopsis transgenic plants

Abstract: Hexokinases (HXKs) and fructokinases (FRKs) are the only two families of enzymes in plants that have been identified as able to phosphorylate Glucose (Glc) and Fructose (Fru). Glc can only be phosphorylated in plants by HXKs, while Fru can be phosphorylated by either HXKs or FRKs. The various subcellular localizations of HXKs in plants indicate that they are involved in diverse functions, including anther dehiscence and pollen germination, stomatal closure in response to sugar levels, stomatal aperture and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…Sucrose down‐regulates WRK4 (triggered by CK), a putative kinase member of the SNF1 KINASE subfamily. CK and glucose trigger the HXK1 pathway for root elongation in Arabidopsis seedlings (Pérez‐Díaz et al, 2021). During glucose application, T6P inhibited ABA synthesis and signaling and acted antagonistically to SnRK1 in Arabidopsis seedlings.…”
Section: Interplay Between Plant Hormone and Sugar Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sucrose down‐regulates WRK4 (triggered by CK), a putative kinase member of the SNF1 KINASE subfamily. CK and glucose trigger the HXK1 pathway for root elongation in Arabidopsis seedlings (Pérez‐Díaz et al, 2021). During glucose application, T6P inhibited ABA synthesis and signaling and acted antagonistically to SnRK1 in Arabidopsis seedlings.…”
Section: Interplay Between Plant Hormone and Sugar Sensorsmentioning
confidence: 99%
“…regulates WRK4 (triggered by CK), a putative kinase member of the SNF1 KINASE subfamily. CK and glucose trigger the HXK1 pathway for root elongation in Arabidopsis seedlings(Pérez-Díaz et al, 2021).During glucose application, T6P inhibited ABA synthesis and signaling and acted antagonistically to SnRK1 in Arabidopsis seedlings. CK antagonizes the ABA signaling by impeding SnRK2 activity through type-B ARRs and, therefore, promotes the seedling establishment(Wang et al, 2021).…”
mentioning
confidence: 99%
“…Hexokinase, a functional regulator of VDAC, has been proven to play a role in pathogen induction and H 2 O 2 -induced cell death in plants [35]. Metabolomics analysis of A. thaliana ectopically expressing the Hxk3 gene showed that phosphorylated sugar (G6P), starch and some metabolites related to the tricarboxylic acid (TCA) cycle are affected [36]. LTP1 plays a role in fatty acid binding and phospholipid and lipid transfer between membranes in vitro [37] and can be strongly induced in Lotus japonicus in response to drought stress [38] and in wheat under cold stress [39].…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the TCA cycle-associated proteins are upregulated under drought stress ( Wang et al., 2019 ). Previous metabolomic analyses have revealed ectopic expression of the Prunus HXK3 gene in Arabidopsis increased the contents of phosphorylated sugars, starch, and some TCA cycle-related metabolites to enhance drought tolerance ( Pérez-Díaz et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%